AB1091 Evaluation of sexual satisfaction in fibromyalgic patients. (23rd January 2014) - Consensi, A.; Rossi, A.; Giacomelli, C.; Conversano, C.; Ferrari, C.; De Feo, F.; Sernissi, F.; Dell'Osso, L.; Bombardieri, S.; Bazzichi, L.
Abstract : Background: FM is a chronic disease affecting predominantly women and characterized by widespread pain, fatigue and several symptoms that may cause severe disability and impairment of quality of life including sexual behaviour. Objectives: The aim of this study was to compare the sexual satisfaction of FM patients with that of healthy controls. Methods: We enrolled 100 women with FM (48±9), and 40 healthy women (42±9). Patients were evaluated by rheumatologists which evaluated clinical parameters (Fibromyalgia Impact Questionnaire, VAS pain, VAS depression, tender points). All subjects were administered the questionnaire "Index of sexual satisfaction" (ISS) (1), a questionnaire that is an indicator of the marital sexual satisfaction and gives indications regarding the emotional aspects of sexual life. High scores of ISS indicate low quality of sexual life and some problems in the sexual part of the marital relationship. In particular the patients with an overall ISS score higher than 30 points (cut-off point) were considered to have sexual dysfunction. Results: The mean ISS score was significantly greater in FM patients (34.23±19.45) than that for healthy controls (23.31±13.20) (p=0.009). The percentage of patients with ISS>30, indicative of sexual dysfunction, was significantly higher for the FM patients (58%) with respect to healthy controls (28%) (p=0.0005). Moreover ISS showed a significant positive correlation with the FIQ score (r=0.31, p=0.005) and VAS depression score (r=0.36, p=0.001). Conclusions: Our results show that FM patients had a poor quality of sexual life, especially concerning the emotional aspects of sexual life, as indicated by the higher ISS score. Emotions definitely play a crucial role in sexual behavior of FM patients, and psychological aspects (depression, anxiety) have surely a great influence on the sexual behavior of FM patients. Understanding the association between FM and sexual dysfunction is fundamental in order to develop prevention and treatment strategies since sexual aspects are an important issue relating to the quality of life. References: Hudson WW et al. J Sex Res. 1981;17:157-174. Disclosure of Interest: None Declared